2013
DOI: 10.1021/es304895z
|View full text |Cite
|
Sign up to set email alerts
|

Emissions of Polycyclic Aromatic Hydrocarbons, Polychlorinated Dibenzo-p-Dioxins, and Dibenzofurans from Incineration of Nanomaterials

Abstract: Disposal of some nanomaterial-laden waste through incineration is inevitable, and nanomaterials' influence on combustion byproduct formation under high-temperature, oxidative conditions is not well understood. This work reports the formation of polycyclic aromatic hydrocarbons (PAHs) and polychlorinated-dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) from incineration of paper and plastic waste containing various nanomaterials, including titania, nickel oxide, silver, ceria, iron oxide, quantum dots, and C60-ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 66 publications
4
58
1
2
Order By: Relevance
“…A similar finding has been reported in the incineration of nano-enabled thermoplastics that contained nanosized metal oxides ( i.e ., titanium dioxide, iron oxide) and carbon nanotubes (28,4042). The authors noticed not only an overall increase in the concentration of PAHs in the released lifecycle particular matter, but a distinct promotion of conversion of LMPAHs to HMPAHs compared to the pristine thermoplastic, which did not contain ENPs (28,41). This unmistakable change in chemical profile towards HMPAHs during thermal degradation of thermoplastics was concluded to be due to the presence of catalytic ENPs.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…A similar finding has been reported in the incineration of nano-enabled thermoplastics that contained nanosized metal oxides ( i.e ., titanium dioxide, iron oxide) and carbon nanotubes (28,4042). The authors noticed not only an overall increase in the concentration of PAHs in the released lifecycle particular matter, but a distinct promotion of conversion of LMPAHs to HMPAHs compared to the pristine thermoplastic, which did not contain ENPs (28,41). This unmistakable change in chemical profile towards HMPAHs during thermal degradation of thermoplastics was concluded to be due to the presence of catalytic ENPs.…”
Section: Resultsmentioning
confidence: 98%
“…The use of various metal/metal oxide ENPs similar to those found in toners and PEPs, such as iron, manganese, titania, zinc and copper have been known to have enhanced catalytic properties due to the increased reactivity and selectivity of these metallic particles (41,4346). It is also worth noting that other particle formation mechanisms involving ozone, in addition to the nano scale metal and metal oxide particles added and released form the toners during printing, have been proposed in previous studies and may also contribute to this VOC transformation phenomenon taking place and reported in this study [(14, 59).…”
Section: Resultsmentioning
confidence: 99%
“…Focussing on nanowaste characterisation, recent studies about end-of-life ENMs, present and measured in the solid phase, aim to examine the fate and potential transformation processes of ENMs during thermal waste treatment processes (Vejerano et al, 2013(Vejerano et al, , 2014(Vejerano et al, , 2015Walser et al, 2012). Currently, only few studies are published that investigated nanowaste in the liquid phase, the transfer of ENMs to liquid phase or their behaviour in landfill leachates (Bolyard et al, 2013;Hennebert et al, 2013;Lozano and Berge, 2012;Walser et al, 2012).…”
Section: Experimental Case Studies On Nanowastementioning
confidence: 99%
“…In the framework of an incineration experiment at laboratory scale, Vejerano et al (2013Vejerano et al ( , 2014 were aiming to examine the influence of ENMs on the formation of PAH, PCDD/F and airborne particulate matter. Waste samples were spiked with ENMs and incinerated at 850°C (see also Vejerano et al, 2014 in Section 4.1).…”
Section: Characterisation Of Nanowaste In the Gas Phasementioning
confidence: 99%
“…Additionally, one paper reported on the formation of the polycyclic aromatic hydrocarbons (PAH) and dioxins from the incineration of paper and plastic waste containing the ENMs, including TiO 2 , NiO, AgNPs, CeO 2 , and C 60 [25]. Depending on the type of waste, the presence of the ENMs in the waste stream resulted in higher emissions of some PAH species.…”
Section: Nanowastes Treatment By Waste Incineration Plantmentioning
confidence: 99%